1997
DOI: 10.1159/000218038
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia Potentiates Antitumor Effect of Thermosensitive-Liposome- Encapsulated Melphalan and Radiation in Murine Melanoma

Abstract: Malignant melanoma are chemoresistant tumors with poor prognosis. The aim of this study was to determine whether multimodality therapy of murine melanoma involving a combination of radiation with thermosen-sitive-liposome-encapsulated melphalan and local hyperthermia would result in enhancement of therapeutic efficacy for a more effective management of melanoma. Melphalan was entrapped in thermosensitive liposomes prepared from natural lipids: egg phosphatidyl choline, cholesterol and ethanol to show phase tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Other drugs including taxol [146], melphalan [147, 148], methotrexate [141, 149], plumbagin [150], dacarbazine [151], mitomycin C [152] and tumor necrosis factor [153], have also been encapsulated (see review by Kong and Dewhirst [154]). Currently only the LTSL-doxorubicin is in clinical trials, but an optimized formulation for cisplatin and other drugs may be possible for the near future.…”
Section: Preclinical and Clinical Studiesmentioning
confidence: 99%
“…Other drugs including taxol [146], melphalan [147, 148], methotrexate [141, 149], plumbagin [150], dacarbazine [151], mitomycin C [152] and tumor necrosis factor [153], have also been encapsulated (see review by Kong and Dewhirst [154]). Currently only the LTSL-doxorubicin is in clinical trials, but an optimized formulation for cisplatin and other drugs may be possible for the near future.…”
Section: Preclinical and Clinical Studiesmentioning
confidence: 99%
“…Some animal experiments have shown that liposomal doxorubicin delivery offers better effectiveness of anticancer treatments than bolus injection, but no obvious advantage over continuous infusion was reported [4]. The development of thermosensitive liposomes to enhance the effectiveness of anticancer treatment has been reported in many studies (e.g., [58]).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in order to further expand the applicability of the heat triggered drug delivery approach to a wider range of solid tumors or possible combination treatments, novel TSL drug formulations should be developed. Examples of other interesting drugs formulated thus far in TSL are cisplatin [51,52], melphalan [53], taxol [54] and miltefosine [55]. These formulations are still in preclinical stages of development and need extensive testing before being applied in the clinic.…”
Section: Timo Lm Ten Hagenmentioning
confidence: 99%